A POOLED DATA ANALYSIS TO DETERMINE RISK FACTORS OF CHILDHOOD STUNTING IN INDONESIA - Tri Siswati; Bunga Astria Paramashanti; Nova Pramestuti; Lukman Waris (Journal of Nutrition College, 2023)
Background: Stunting among children remains a public health concern in Indonesia, where the prevalence of stunting in rural areas is higher than in urban areas.Objectives: This study aimed to analyze risk factors for stunting and severe stunting among children aged 0-59 months in rural and urban Indonesia.Method: This cross-sectional study used pooled datasets from Indonesia’s Basic Health Research in 2007, 2010, and 2013. Our study samples included 38,246 children aged 0-59 months whose height-for-age Z-score (HAZ) was between -5.99 and 5.99 standard deviations. The primary outcomes were stunting and severe stunting, whereas dependent variables included factors at the child, household, and community levels. We apply Stata 13 for univariate, bivariate, and multivariate analysis.The prevalence of stunting and severe stunting was higher in rural than urban areas. On one hand, risk factors significantly associated with stunting and severe stunting in urban areas were low birth weight, maternal height, informal father’s occupation, low economic level, and children from East Indonesia and Sumatra. Furthermore, the father’s height was only associated with stunting, while the number of children >3 was only associated with severe stunting. On the other hand, risk factors age, low birth weight, maternal height, father’s height, household member 5-9 people, middle and low economic level were significantly associated with stunting and severe stunting in rural areas. Moreover, poor WASH was only associated with stunting, while informal mother occupation, low father education, number of household members > 9 people, and living in Sumatra and East Indonesia were associated with severe stunting in rural areas.Conclusion: Low birth weight, short parents, and economic income were risk factors for stunting and severe stunting children in urban and rural areas. Keywords: Children; Pooled data; Risk factors; Stunting